2009
DOI: 10.1099/jmm.0.010033-0
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of plasmid-mediated quinolone resistance determinants in commensal members of the Enterobacteriaceae in Ho Chi Minh City, Vietnam

Abstract: Antimicrobial-resistant pathogenic members of the Enterobacteriaceae are a well-defined global problem. We hypothesized that one of the main reservoirs of dissemination of antimicrobial resistance genes in Vietnam is non-pathogenic intestinal flora, and sought to isolate antimicrobial-resistant organisms from hospitalized patients and non-hospitalized healthy individuals in Ho Chi Minh City. The results identified substantial faecal carriage of gentamicin-, ceftazidime- and nalidixic acid-resistant members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 38 publications
2
54
1
Order By: Relevance
“…However, they were detected at a very low rate from Salmonella in France [4] and the U.S.A. [16]. In addition, there were several reports on Enterobacteriaceae harboring quinolone-resistant genes in Vietnam [26] and other countries [32]. These reports confirmed that PMQR genes in foodborne isolates may play a role in the spread of quinolone resistance through the food chain.…”
Section: Discussionmentioning
confidence: 83%
“…However, they were detected at a very low rate from Salmonella in France [4] and the U.S.A. [16]. In addition, there were several reports on Enterobacteriaceae harboring quinolone-resistant genes in Vietnam [26] and other countries [32]. These reports confirmed that PMQR genes in foodborne isolates may play a role in the spread of quinolone resistance through the food chain.…”
Section: Discussionmentioning
confidence: 83%
“…Recent surveillance reports from Asian countries estimate a prevalence of 30% to 74% of fluoroquinolone resistant E. coli in China and Japan, and a 74% rate of nalidixic acid resistance in Vietnam. 16,18,19 Due to the small numbers of these higher risk subgroups our ability to detect a statistically significant difference was decreased and a larger study population is needed to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have observed carriage rates of Enterobacteriaceae resistant to third-generation cephalosporins and/or gentamicin in stool samples from up to 90 % of healthy people in HCMC [23]. …”
Section: Discussionmentioning
confidence: 99%